Serum status of selenium and chromium in patients with cardiovascular diseases and controls in Iraq. - Al Doori, Kassim M. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: The importance of essential trace elements plays a major role in medicine mainly cardiovascular diseases. Methods: The study involved 305 patients with either myocardial infarction ( MI ) , angina pectoris ( AP ) or hypertension ( HT ) for evaluation of these trace elements level ( Se & Cr ) as compared with 100 control subjects in Ibin Al Bitar hospital for cardiac surgery between July 2003 and May 2005 by using Atomic Absorption Spectrophotometer ( AAS ) done in the laboratories of ministry of Sciences and Technology in Baghdad. Result: The total numbers of patients enrolled in this study were 305 patients, Ml contributes to 70 patients, 55 male and 25 female with mean age of 60 ± 20 and 58 ± 19 years respectively. Unstable angina contribute to 105 patient in which 70 of them were male with mean age of 63 ± 20 years and 35 female with mean age of 60 ± 19 years and 120 hypertensive patient in which male contribute to 90 with mean age of 64 ± 19 years and the other 30 were female with mean age of 48 ± 13 years, those 305 patients were compared with 100 normotensive control subject in which 65 of them were male with mean age of 56 ± 20 years and the remaining 35 were female with mean age of 46 ± 13 years. The analysis of results show that the level of Se and Cr were significantly lower in both sexes in patient with MI, AP and HT as compared with control, and the concentrations of Se were even much lower in acute MI as compared with AP. Conclusion: The concentrations of trace elements Se and Cr were significantly lower in patients having MI, AP and HT as compared with controlled normotensive persons, besides the concentration of Se was much lower in MI as compared with cases of AP.